Eksplorasi Hambatan Komunikasi Matematis Siswa melalui Penerapan Think Pair Share di MTsS KP. Beusa - Rizayanti (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study aims to explore students’ mathematical communication barriers through the implementation of the Think Pair Share (TPS) learning model at MTsS Kampung Beusa . The research employed a qualitative descriptive method involving 25 students of class VII during the 2024/2025 academic year. Data were collected through mathematical communication tests, interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that the application of the Think Pair Share model effectively improved students’ mathematical communication skills. Before applying TPS, students tended to face barriers such as difficulty expressing ideas, lack of confidence, and limited use of mathematical symbols and representations. After implementing the TPS model, students demonstrated significant improvement, with the average score increasing from 65.4 (fair) to 79.6 (good), indicating an average gain of 14.2 points. The stages of think, pair, and share allowed students to think independently, discuss collaboratively, and share ideas confidently in class. This process not only enhanced communication ability but also strengthened reasoning, cooperation, and self-confidence. Therefore, the Think Pair Share model can be considered an effective approach to minimize communication barriers and foster students’ active participation in mathematics learning.